Valence state of Sm in single-crystalline EuO thin films. (6th April 2017) - Reisner, A.; Kasinathan, D.; Wirth, S.; Tjeng, L. H.; Altendorf, S. G.
Abstract: Samarium has two stable valence states, 2+ and 3+, which coexist in many compounds forming spatially homogeneous intermediate valence states. We study the valence state of samarium when incorporated in a single crystalline EuO thin film which crystallizes in a fcc structure similar to that of the intermediate valence SmO, but with a larger lattice constant. Due to the increased lattice spacing, a stabilization of the larger Sm 2+ ion is expected. Surprisingly, the samarium incorporated in Sm x Eu1− x O thin films shows a predominantly trivalent character, as determined by x-ray photoelectron spectroscopy and magnetometry measurements. We infer that the O 2− ions in the EuO lattice have enough room to move locally, so as to reduce the Sm-O distance and stabilize the Sm 3+ valence.